2021
DOI: 10.2169/internalmedicine.6216-20
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of a Self-expandable Metallic Stent Inserted for Malignant Gastric Outlet Obstruction

Abstract: Duodenal stenting has gradually been established as the first-line treatment for malignant gastric outlet obstruction (GOO). We encountered a case of duodenal stent fracture in a 76-year-old woman with gastric cancer and GOO. She underwent self-expandable metallic stent (SEMS) placement. The SEMS was found to be fractured 4 weeks after its placement. We removed the broken part of the stent and placed a second SEMS. SEMS fracture is a rare and-to the best of our knowledge-unreported complication; hence, clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…According to previous reports, the incidence of stent fractures in patients with mGOO ranges from 0.0% to 4.8% (7). Stent fracture is an infrequent complication in patients with mGOO, and few case reports have described the management and outcomes of stent fracture (8)(9)(10). However, the mechanism underlying stent fracture remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to previous reports, the incidence of stent fractures in patients with mGOO ranges from 0.0% to 4.8% (7). Stent fracture is an infrequent complication in patients with mGOO, and few case reports have described the management and outcomes of stent fracture (8)(9)(10). However, the mechanism underlying stent fracture remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports have hypothesized that metal fatigue (e.g. the stress applied by the endoscopic procedure to the stent, gastric acid, removal of the stent coating material by re-interventions, and repeated and prolonged shearing forces caused by gastrointestinal motility), selection of stents with low axial force, and manufacturing defects can induce stent fracture (8)(9)(10). Kadokura et al (10) suggested that it may be useful to select a stent with a stronger axial force or to select a shorter stent to reduce the risk of fracture in cases of short stenosis in bending sites, such as at the gastric outlet (prepyloric region to the duodenum).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, SEMS with the highest axial forces were not found to be associated with any of the reported fracture cases. To that effect, Kadokura et al recommended the use of shorter stents with higher axial forces to avoid fractures in duodenal SEMS [ 39 ]. However, Hirdes et al express concern that stents with higher axial force can cause luminal wall injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%